Perhitungan Beban Pendinginan pada Ruang Akomodasi Kapal General Cargo KM Pratiwi 2055 DWT - Suyanto, Suyanto; Wibowo, Riyanto (Marine Science and Technology Journal, 2024)
The use of HVAC on ships is very necessary considering that the environmental conditions are relatively hot when the ship is operated, so to provide comfort to the ship's crew it is necessary to ensure that the temperature and humidity of the ship's accommodation spaces are maintained. One of the main problems in HVAC planning is determining the right cooling machine capacity, so that the cooling goal of providing cool and comfortable air conditions can be achieved. The selection of cooling engine capacity is chosen based on the total cooling load on the ship. The cooling load calculation is carried out using equations and calculation steps in accordance with ISO 7547 of 2002. The existing heat load sources are the total of the transmission heat load that propagates through the walls, ceiling and floor of the room, the heat load from the room occupants, the radiation heat load that passes through the room. walls, heat load from room lighting, and heat load from electronic equipment used in the room. Calculation of the cooling load for the accommodation space of the General Cargo KM Pratiwi 2055 DWT ship identified transmission heat of 3528 Watts, room occupant heat of 9910 Watts, radiant heat through the walls of 3700 Watts, room lighting heat of 1340 Watts, and heat load from equipment electronics of 5900 Watts. The total cooling load from the cooling machine is 24,378 Watts.